1987
DOI: 10.1093/ajcn/46.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in plasma branched-chain keto acid levels in obesity

Abstract: Obesity was associated with a significant increase in postabsorptive plasma concentrations of the branched-chain keto acids in men but not in women matched for body-mass index and age. Plasma glucose and serum insulin were significantly higher in obese subjects than in nonobese control subjects. Obese women had more adipose tissue than did obese men from the sum of triceps and subscapular skinfold thickness. It is suggested that augmentation in plasma branched-chain keto acids in obesity may reflect insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…We found elevated plasma BCAAs in ob/ob mice and high-fat diet-induced obesity in mice and in Zucker fatty rats, in agreement with previous reports in obese humans and Zucker fatty rats (4,5,11,12,37,46,48,49,52,56). These elevations were associated with reductions in the activity or amount of enzymes involved in the early steps of BCAA metabolisms in selective tissues, including liver and fat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found elevated plasma BCAAs in ob/ob mice and high-fat diet-induced obesity in mice and in Zucker fatty rats, in agreement with previous reports in obese humans and Zucker fatty rats (4,5,11,12,37,46,48,49,52,56). These elevations were associated with reductions in the activity or amount of enzymes involved in the early steps of BCAA metabolisms in selective tissues, including liver and fat.…”
Section: Discussionsupporting
confidence: 92%
“…obesity; mitochondrial branched chain amino acid transaminase; branched chain keto acid dehydrogenase; branched chain keto acid dehydrogenase kinase; ob/ob mice; Zucker rats; bariatric surgery; humans PLASMA CONCENTRATIONS of branched-chain amino acids (BCAAs) are elevated in humans and animal models of obesity (4,11,12,31,37,46,48,52,56). Although the plasma levels of other amino acids may also change in obesity, the rises in the BCAAs are of particular interest because they appear to have unique obesity-related effects.…”
mentioning
confidence: 99%
“…On the one hand, many reports have suggested that increased levels of BCAA have beneficial effects on various aspects of obesity and metabolic syndrome including satiety and glycemia (33)(34)(35). On the other hand, several studies link elevated BCAA levels with obesity and extent of insulin resistance (36)(37)(38). Additional evidence demonstrates that BCAA metabolism plays a critical role in regulating adipocyte differentiation and lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Open field test was used to assess activity levels and anxiety‐like behavior (Schauder, Zavelberg, Langer, & Herbertz, 1987). Animals were placed in a square enclosure 40 cm by 45.1 cm with walls 34.9 cm high and allowed to explore freely for 10 min.…”
Section: Methodsmentioning
confidence: 99%